Design and Development of an Automatic T-Shirt Folding Tool Based on the Arduino Uno Microcontroller - Aan Priyadi; Marzuki, Imam; Aprilia, Ira (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2022)
One of the household chores that is concerned about this problem is folding the t-shirt from the drying process. When there are lots of stacks of t-shirts, especially for laundry entrepreneurs. Manually folding a t-shirt will certainly look less presentable if done very quickly. The purpose of this study is to accelerate the activity of the laundry  entrepreneur,  therefore a  model  of  tool  that can  help  in t-shirt  folding  quickly  with  a  workforce is automatically  created.  Using  six  servo  motors  as  a  folding  drive  on  the  right,  left  and  bottom.  To  start  the process  when  the  tool  is  used,  by  utilizing  an  ultrasonic  sensor  to  start  and  stop  the  folding  process automatically.  The components in this  study  are  controlled by the  Arduino  UNO  microcontroller  so  that  it  can work automatically in accordance with the commands that have been applied. There are ten tests using t-shirts of the same size. So the results of the ten testing processes carried out a folding duration of about 3 seconds with 1 t-shirt, 9 seconds by folding 3 t-shirts, 15 seconds by folding 5 t-shirts, 21 seconds by folding 7 t-shirts, and 30 seconds  by  folding  10  t-shirts.  It  can  be  concluded  that  folding  a  t-shirt  using  this  tool  feels  faster  and  neater than the manual folding process.